Ferroptosis of CD163+ tissue-infiltrating macrophages and CD10+ PC+ epithelial cells in lupus nephritis - Cheng, Qi; Mou, Lijun; Su, Wenjing; Chen, Xin; Zhang, Ting; Xie, Yifan; Xue, Jing; Lee, Pui Y.; Wu, Huaxiang; Du, Yan (Frontiers in Immunology, 2023)
Background Dysregulation of cell death and defective clearance of dying cells are closely related to the pathogenesis of lupus nephritis (LN). However, the contribution of a recently discovered form of programmed cell death (PCD) called ferroptosis to LN has not been explored in detail. The purpose of this study was to investigate the role of ferroptosis and its associated metabolic pathways in the pathogenesis of LN. Methods The composite gene expression scores were calculated by averaging the z-scored transformed log2 expressed genes within each form of PCD and pathway. Immunohistochemistry and immunofluorescence assays were used to verify the bioinformatics results. Results We determined that ferroptosis is prominently and specifically elevated in the glomerular compartment of LN patients compared to other forms of PCD and kidney disease. This finding was then verified by immunohistochemical staining of 4-HNE (a key indicator for ferroptosis) expression in our own cohort (P < 0.0001). Intercorrelation networks were observed between 4-HNE and blood urea nitrogen, SLE disease activity index, serum creatinine, and complement 4, and negatively correlated with glomerular filtration rate in our own LN cohort (P < 0.05). Furthermore, enhanced iron metabolism and reduced fatty acid synthesis may be the most important factors for ferroptosis within the glomerulus. Through analysis of a single cell sequencing dataset and verification of immunohistochemical and immunofluorescence staining, aberrantly activated lipid peroxidation in CD163+ macrophages and CD10+ PC+ (pyruvate carboxylase) epithelial cells indicated that they may be undergoing ferroptosis in the glomerular compartment. Conclusions Two dysregulated genes, CD163 and PC, were identified and verified that were significantly associated with lipid peroxidation. Targeting ferroptosis in CD163+ macrophages and CD10+ PC+ epithelial cells may provide novel therapeutic approaches in LN.